Analisis Wacana Kritis atas Keberpihakan Media Kompas.com dan Detik.com pada Pemberitaan Program Makanan Bergizi Gratis (MBG) oleh Prabowo Subianto - Sofia Nur Khasanah; Muhammad Badrus Siroj (EduInovasi: Journal of Basic Educational Studies, 2025)
The purpose of this study is to examine how Kompas.com and Detik.com frame Prabowo Subianto's Makanan Bergizi Gratis (MBG) utilizing Teun A. van Dijk's Critical Discourse Analysis technique. This study's data sources include six news texts, three from Kompas.com and three from Detik.com. The approach examines three layers of discourse structure: macrostructure, superstructure, and microstructure, to determine how subjects, news flow, and language choices are employed to build meaning. The findings reveal that both media portray the MBG in a good light, but with distinct characteristics. Kompas.com stresses the MBG's technocratic and administrative characteristics, presenting it as an organized and responsible program through the use of formal language and quantitative statistics. Detik.com, on the other hand, takes a more personal and emotional approach, highlighting Prabowo's community connections and intimate knowledge of dietary difficulties. This study finds that media bias may manifest itself through non-explicit linguistic patterns and presenting tactics. This study suggests the need for more fair reporting and more research with larger media attention.